Effect of iron ions as assistant depressant of citric acid on the flotation separation of scheelite from calcite. (21st September 2021) - Dong, Liuyang; Wei, Qian; Qin, Wenqing; Jiao, Fen
Highlights: Scheelite and calcite had good floatability using sodium oleate as collector. Citric acid lacked selectivity in inhibiting the two minerals. Iron ions was used as assistant depressant of citric acid. Iron ions and citric acid was selective co-adsorbed on the surface of calcite. Flotation separation of scheelite from calcite was achieved using Fe 3+ /CA. Abstract: The flotation separation of scheelite and calcite is challenging, because of the similarities in their surface chemical properties, solution chemical properties, calcium ion active sites, and, consequently, floatability. Efficient flotation depressants are required to separate scheelite and calcite by flotation. Citric acid (CA) has recently been investigated as a flotation depressant; however, its depressing action toward calcite is limited owing to its low number of polar groups (i.e., carboxyl and hydroxyl groups). In this study, iron ions (Fe 3+ ) were used to improve the depressing action and selectivity of CA toward calcite. The microflotation behavior of scheelite and calcite was investigated under the influence of different depressant systems. Wettability, Fourier transform infrared, X-ray photoelectron spectroscopy, thermodynamic, and atomic force microscopy analyses revealed the selective depression mechanism of the depressant mixture comprising Fe 3+ and CA (denoted Fe 3+ /CA). The microflotation results indicate that although the flotation separation of the two minerals is difficult using CA on its own, good separation effect is achieved using Fe 3+ /CA. Fe 3+ /CA chemically co-adsorbs on the calcite surface more strongly than on the scheelite surface. The iron ions and CA form ferric citrate (where L here denotes that the citrate ion is a ligand) that is then adsorbed at the oxygen sites on the surface of calcite in the flotation slurry. In the presence of Fe 3+ /CA, the adsorbed complexes form a dense layer on calcite, but a sparse layer on scheelite. The proposed depressant system realizes the efficient flotation separation of scheelite from calcite, which has theoretical and practical significance for the efficient development and utilization of scheelite resources.